Development of the citizens measure into a tool to guide clinical practice and its utility for case managers - Bellamy, Chyrell; Kriegel, Liat; Barrenger, Stacey L.; Klimczak, Michele; Rakfeldt, Jaak; Benson, Victoria; Baker, Michaella; Benedict, Patricia; Williamson, Bridgett; MacIntyre, Gillian (American Journal of Psychiatric Rehabilitation, 2017)
A measure of citizenship was developed and validated by Rowe and colleagues (O’Connell, Clayton, & Rowe, 2017). The items clustered around the 5 Rs of citizenship as defined by Rowe et al.: relationships, rights, resources, roles, and rights, and a sense of belonging. Although a measure has its utility in clinical settings, to address time constraints and other administrative burdens expressed by providers in their day-to-day practice, a citizens tool was developed as a practical way that providers can enhance dialogue between providers and clients on citizenship for clients served in mental health and criminal justice reentry settings. This article describes the development of the tool, testing of the tool’s utility with case managers, and implications for practice. © 2017 Taylor & Francis.
8 citations (Crossref) [2023-10-31] Citation Key Alias: pop00114 tex.type: [object Object]
Keywords: Article; adult; case management; case manager; citizenship; clinical practice; community inclusion; community integration; dept.swk; evidence based medicine; female; human; major clinical study; male; marginalized communities; mental capacity; mental disease; mental health service; poverty; practical clinical tools; priority journal; psychological well-being; self concept; social support; socioeconomics; translational research